(untitled) (Journal of Environmental Microbiology and Toxicology, 2018)
Nitrophenols (NPs) is one the most widely used chemical compounds due to their mass usage in agricultural industry, medical applications and domestic activities. However, due to their intensive application in these industries, many reports have been arising in regard to the toxicity effects towards human health and the environments. It has been acknowledged that various microbial species were able to utilize the NPs as their sustenance are being exploited for their mechanistic approach. Current research has been focused on the isolation of those strains and the study of microbial species of potential environmental and biological impact. This review highlights on one of the examples of polynitrophenols - 2,4-dinitrophenol (2,4-DNP), their usage in recent industry, implications of 2,4-DNP to the human health and environmental niche, and role of 2,4-DNP-utilising microbes in current bioremediation.